A Comparative Study to Check Students' Linguistics Achievement in Face-to-Face and Online Learning at BS Level - Nisa, Mehr-un-; Nouman, Sana; Ashraf, Rabbia; Haroon, Wuzna (Pakistan Journal of Humanities and Social Sciences, 2024)
This study aimed was to conduct a comparative analysis of the linguistic achievement of students in traditional learning (face to face) and virtual learning (online) at the BS level. It was hypothesiszed that there is likeliy to be a difference in studnets linguistics achievement in face- to- face (traditional) and online learning (virtual). The final term papers of students in both modes of learning are examined to find out the most common errors that pupils make. Due to the sudden outbreak of Covid-19, there has come an obvious transition in the patterns of teaching and learning. With this pandemic and its subsequent lockdowns, as well as isolated contact, e-learning has become a fundamental tool in ensuring continuity of education. This revolution to the online system has urged the researcher to analyze the linguistic achievement of students by comparing face to face and online learning. This study is based on comparative analysis and the data for this present study is collected from 120 students, 60 from face to face classes, and 60 from online classes. The analysis is done on the overall marks obtained by students to see the difference in achievements as well as the errors in writing in the face to face and online learning. The findings of the results showed significant difference in both types of learning. After evaluating the results, it is recommended that there is a dire need for the development of online training programs for both teachers as well as students. This research concludes that the learning outcomes of students are much better in the face to face setting as compared to online learning.